2021
DOI: 10.26803/ijlter.20.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Student Response Systems in a Technology Enhanced Flipped Classroom: A Qualitative Investigation in Higher Education

Abstract: Disruptive technology and a generation with an increased interest in using that technology to aid their learning has caused a need to change the current educational landscape. Student Response Systems are a contemporary means to integrate digital technology in the modern classroom. The purpose of this qualitative study is to examine the perspectives that impact students' engagement when using Student Response Systems in a technology enhanced classroom environment. The study was guided by qualitative methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…As flipped learning combines traditional classroom with online instruction; there emerges a complexity in terms of the variety and diversity of learning environments, learning design(s) and as well as learning styles of the students (Dantas & Cunha, 2020) and narrow awareness. Similarly, cultural and technological diversity and the Net-Generation experiences create problems for flipped learning and its success (Åhman & Nguyen, 2020). Likewise, after reviewing research experiences of university students in flipped learning, Chen et.…”
Section: Introductionmentioning
confidence: 99%
“…As flipped learning combines traditional classroom with online instruction; there emerges a complexity in terms of the variety and diversity of learning environments, learning design(s) and as well as learning styles of the students (Dantas & Cunha, 2020) and narrow awareness. Similarly, cultural and technological diversity and the Net-Generation experiences create problems for flipped learning and its success (Åhman & Nguyen, 2020). Likewise, after reviewing research experiences of university students in flipped learning, Chen et.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results of this study are compatible with those of past research, such as Nasution's (2021) study, which demonstrated that teachers have a high level of expertise. In addition, Peter (2019); Dewi (2020) revealed that instructors must be competent in all aspects of the teaching and learning process, especially in terms of cognitive abilities Ahman (2021). found that 94.4% of respondents were aware of the formation in her study on the level of preparedness of mathematics teachers in Johor Bahru for implementing the standard primary school mathematics curriculum.…”
mentioning
confidence: 99%